Density of Clams (Polymesoda sp.) in the Mangrove Ecosystem of Pinotu Village, Toribulu District, Parigi Moutong Regency - Niwana, Nuning; Masrianih,; Sabran, Moh.; Sutrisnawati,; Zainal, Syech; Dhafir, Fatmah (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to assess the density of Polymesoda sp. in the mangrove ecosystem of Pinotu Village, Toribulu District, Parigi Moutong Regency, an area experiencing habitat pressure due to environmental change. A quantitative descriptive approach was applied using purposive sampling across three stations: Station 1 behind the residential area, Station 2 in the central mangrove zone, and Station 3 near shrimp ponds. Sampling was conducted at low tide using a line transect method with zigzag plots. Each station consisted of three 25 m transects spaced 10 m apart, with five 1 m² plots established along each transect, yielding a total of 45 observation plots. Environmental parameters measured included temperature, salinity, and pH. The highest density of Polymesoda sp. was recorded at Station 2 (2.93 ind/m²), followed by Station 1 (1.87 ind/m²), whereas the lowest density was observed at Station 3 (0.87 ind/m²). Differences in density were associated with habitat variation, particularly mangrove vegetation density, substrate characteristics, and environmental physical and chemical conditions. These findings indicate that more stable and better-preserved mangrove habitats support higher densities of Polymesoda sp., highlighting the importance of habitat quality in sustaining its population.